Never heard that before: interventional strategies to improve anatomical knowledge in nursing students - Narnaware, Yuwaraj; Neumeier, Melanie (My University, 2022)
Bioscience problem? The medical & allied-health students worldwide reported a growing concern over the loss of bioscience knowledge of first-year of their degree program. They lose approx. 50-80% of the first-year anatomical knowledge within two or more years of medical school. Ninety-two (92%) of second year medical students reported that anatomical knowledge was very helpful. Only 14.0% of the final year medical students felt confident in their first-year anatomy knowledge. Knowledge retention studies have not yet been assessed in nursing students. Objectives: assess the anatomical knowledge acquisition in the first-year nursing students and its transfer/loss, retention, and application in the second year. Identify factors impacting knowledge acquisition, retention, and application. Discuss robust interventional strategies to bridge the gap between first-year theory and second-year of nursing.
Presented on May 12, 2022 at the Faculty of Nursing Research Day held at MacEwan University in Edmonton, AB, Canada.
Keywords: nursing students; bioscience knowledge